'This Tragically Obscured Summer': News Media and Uncertainties of Veracity in the 1928 Nobile/Amundsen Disaster. Issue 1 (2nd January 2021) - Ytreberg, Espen
Abstract : The summer of 1928 was marked by two internationally reported and disastrous events involving two polar explorers: the crash and rescue of Umberto Nobile's airship 'Italia' in the polar regions of the North Atlantic ocean, and the death of the Roald Amundsen, en route to rescuing Nobile. The article discusses these disasters as indicative of a historical moment in the mediation of events where technological and logistical developments enabled a continuous news coverage of radically remote locations. It argues that these new affordances came with an increased and pervasive sense of uncertainty about the veracity of factual information. Analyzing Norwegian newspaper coverage, the article finds a range of articulations of this uncertainty, including a preoccupation with rumours and speculations, as well as with chronic difficulties in determining factual veracity.